Spatial model of potential areas for avocado plantations in the State of Mexico - Figueroa-Figueroa, Dulce Karen; Ramírez-Dávila, Jose Francisco; Antonio-Némiga, Xanat; Serrato-Cuevas, Rodolfo (Revista Mexicana de Ciencias Agrícolas, 2024)
Abstract In recent years, avocado has become one of the most important and demanded crops internationally, Mexico has 30% of the world’s production and the State of Mexico is the third producer nationwide, a situation that favors the excessive expansion of this crop in the state. For this reason, this research aimed to identify regions with optimal and suboptimal potential for the establishment of avocado plantations in the municipalities of: Coatepec Harinas, Donato Guerra, Temascaltepec and Tenancingo in the State of Mexico. The study was carried out in three stages, the integration of a geospatial database in the environment of geographic information systems, the construction of criteria for the analysis and weighting of territorial variables, and the development and validation of a potential allocation model for avocado crops. As a result, the areas that showed optimal potential represent a total of 9 543.82 ha, located south of the municipalities, distributed as follows: 3 261.2 ha in Coatepec Harinas, 2 973.87 ha in Temascaltepec, 2 124.41 ha in Donato Guerra, and 1 184.33 ha in Tenancingo. The areas with suboptimal potential represent a total of 6 098.54 ha, of which Coatepec Harinas has 2 183.63 ha, Temascaltepec 1 846.41 ha, Donato Guerra 1 326.34 ha, and Tenancingo 742.16 ha. The high potential of the different municipalities of the State of Mexico does not indicate that the entire area has the right conditions for the establishment of avocado crops.